Views and experience of communication when receiving a serious mental health diagnosis: satisfaction levels, communication preferences, and acceptability of the SPIKES protocol - Milton, A.; Mullan, Barbara (Informa Healthcare, 2016)
Background: There is limited research investigating how information about a mental health diagnosis is discussed and received. Aims: To measure community-based service users’ satisfaction and preferences toward receiving news of a serious mental health diagnosis and to assess the acceptability of a diagnostic communication protocol (SPIKES: Setting; Perception; Invitation; Knowledge; Empathy; Summarizing). Method: A survey was conducted with 101 participants. Results: Participants rated the methods clinicians use to facilitate diagnostic discussions are highly important; however, they were not wholly satisfied with their experience. Higher satisfaction was reported if participants were provided with information in a face-to-face meeting (p < 0.001), and if they received supplementary support at the time of diagnosis from additional health professionals rather than only a sole practitioner (p < 0.001). The SPIKES protocol was rated as highly acceptable, with Empathy being rated as the most important feature. Conclusions: This research indicates there were specific areas of communication practices which can be improved within mental health service provision, as a gap existed between participants’ desire for support and their experience. Strategies outlined in the SPIKES protocol, and others such as addressing stigma concerns, may prove useful in development of clinician training and service improvement.